2017
DOI: 10.2320/jinstmet.j2016063
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a TiAl<sub>3</sub> Layer by an AIH-FPP Treatment Using Mechanically Milled Particles and Its Wear Resistance

Abstract: In order to form a Ti-Al intermetallic compound layer on a carbon steel surface, an atmospheric-controlled induction heating fine particle peening (AIH-FPP) treatment was performed at 1000℃ in argon atmosphere. The shot particles were prepared by a mechanical milling method. Titanium and aluminum particles at molar ratios of one to three were mechanically milled by a planetary ball mill for 6 h. The treated surface was analyzed using a scanning electron microscope, an energy dispersive X-ray spectrometer and X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…In previous work, voids have been observed to form in the surface layer when mechanically-milled Ti/Al particles were used. 12) In contrast, in the present study, a dense layer was created as a result of including Ni in the shot particles. This result can likely be explained by the heat generated by the combustion synthesis reaction between Al and Ni.…”
Section: Analysis Of the Intermetallic Compound Layer Resulting From contrasting
confidence: 55%
See 2 more Smart Citations
“…In previous work, voids have been observed to form in the surface layer when mechanically-milled Ti/Al particles were used. 12) In contrast, in the present study, a dense layer was created as a result of including Ni in the shot particles. This result can likely be explained by the heat generated by the combustion synthesis reaction between Al and Ni.…”
Section: Analysis Of the Intermetallic Compound Layer Resulting From contrasting
confidence: 55%
“…6,7) Our work has recently shown that intermetallic compound layers can be produced on the surface of carbon steel by AIH-FPP treatment via a combustion synthesis reaction 8,9) that occurs on the surface of the treated material. 10,11) We have also proposed that mechanically-milled shot particles containing different elements could be used to create homogeneous intermetallic compound layers. 10) In previous work, intermetallic compound layers having a minimal concentration of voids were created on titanium alloy surfaces upon applying the AIH-FPP treatment, based on mechanically-milled pure titanium and aluminum particles mixed with nickel based alloy particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In AIH-FPP, an induction-heated metal is subjected to fine particle peening (FPP) under an arbitrary atmosphere. Layers containing intermetallic compounds such as Ni-Al 10) and Ti-Al [11][12][13][14] without non-reacted metallic elements can be formed on the surfaces of the carbon steel 10,11) or titanium alloy [12][13][14] within a few minutes. The modified layers improve the wear resistance and high-temperature oxidation resistance of the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The modified layers improve the wear resistance and high-temperature oxidation resistance of the substrates. 10,11,13) Possible mechanisms for the rapid formation of the intermetallic compound layer include the occurrence of combustion synthesis reactions between the elements of the shot particles and substrate 13) or diffusion of the shot particle elements transferred to the surface into the substrate. 14) Based on the previous studies, the application of AIH-FPP with shot particles containing aluminum is expected to form an Fe-Al intermetallic compound layer on stainless steel surfaces rapidly, and the tribological properties of the steel would be improved.…”
Section: Introductionmentioning
confidence: 99%